1999
DOI: 10.1177/00912709922012015
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Administration of the Erythromycin Breath Test (EBT) and Oral Midazolam as In Vivo Probes for CYP3A Activity

Abstract: Given the prominent role of CYP3A in the metabolism of drugs, it is important to identify whether new chemical entities will affect this enzyme system and produce clinically relevant drug interactions. This study evaluated concomitant administration of intravenous [14C N-methyl] erythromycin (3 microCi) (erythromycin breath test; EBT) and 2 mg oral midazolam as probes of systemic and of systemic plus presystemic CYP3A activity, respectively. Twelve males received the probes in a two-period crossover fashion: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 16 publications
2
54
0
Order By: Relevance
“…Therefore, we assumed that intraindividual variation of N 2 and N 3 was not so large. For oral midazolam clearance, McCrea et al (1999) reported that intrasubject CV% for midazolam AUC 0-last was 16.9%. However further studies of larger sample sizes, including females and people of different generations, are needed to evaluate the usefulness of N 2 and N 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we assumed that intraindividual variation of N 2 and N 3 was not so large. For oral midazolam clearance, McCrea et al (1999) reported that intrasubject CV% for midazolam AUC 0-last was 16.9%. However further studies of larger sample sizes, including females and people of different generations, are needed to evaluate the usefulness of N 2 and N 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Formation of a minor primary metabolite, 4-hydroxymidazolam, and of a minor secondary metabolite 1ø, 4-dihydroxymidazolam, are also catalyzed by CYP3A, and these together, as glucuronide conjugates, comprise another 4% to 6% of the administered dose (Gorski et al 1994b). It has been suggested that the pharmacokinetics of midazolam following oral administration can be used as a cumulative measurement of CYP3A activity in the small intestine and liver (Wandel et al 1998;McCrea et al 1999). But midazolam clearance is also inconvenient in a daily clinical situation due to its necessity for periodical blood sampling.…”
mentioning
confidence: 99%
“…The KTZ-MDZ interaction model was used to simulate five published KTZ-MDZ studies. These studies were designed to evaluate the effect of KTZ on MDZ AUC following a single 200-mg dose of KTZ, administered simultaneously or 2 h before MDZ (McCrea et al, 1999), 200 mg of KTZ every 12 h for 2 days, administered simultaneously (Tsunoda et al, 1999) or 12 h before MDZ (Eap et al, 2004), 200 mg of KTZ given once a day for up to 12 days (Lam et al, 2003), and 400 mg of KTZ administered once a day for 4 days (Olkkola et al, 1994). The ratio of MDZ AUC in the presence of KTZ to MDZ AUC in the absence of KTZ was used as a measure of inhibitory response.…”
Section: Methodsmentioning
confidence: 99%
“…Mean (SD) daily urine volume (ml) following tolvaptan or placebo alone or following co-administration with ketoconazole or rifampicin 43% decrease observed by McCrea et al [18] using the same regimen. A 30 mg dose of tolvaptan produced no change in the ERBT.…”
Section: Tablementioning
confidence: 97%